Cartography science of making maps - Nichollas, Tucker (2017)
Cartography concerns itself with the study and application of making maps. It is an important practice in the fields of transportation and circumnavigation, military and research-related purposes. The book aims to shed light on some of the fundamentals concepts of cartography. It is specifically designed for the students to learn details about this field. This book is a valuable compilation of topics, ranging from the basic to the most complex theories and principles of the area. The topics covered in this extensive book deal with the core subjects of cartography. Through this text, we attempt to further enlighten the readers about the new techniques in this field.